Legal Regime of Ballast Water in Colombia - Lastra Mier, Roberto; vergara castano, alba ruth; Cardona Gonzalez, Alvaro Hernando (Revista Ciencias Marinas y Costeras, 2025)
In the context of globalization, 80% of world trade is conducted via the oceans. This implies that navigation constitutes not only one of the drivers of the global economy but also one of the factors with the greatest impact on marine ecosystems. From a technical navigation perspective, ships require mechanisms to stabilize themselves and their cargo, which is achieved by filling or emptying their bilges at will using ballast water. Large volumes of water are transported from departure ports to destination ports, indirectly carrying large quantities of microorganisms, some of which are pathogenic and are mostly considered invasive species. These organisms not only alter the ecosystems into which this water is discharged but also pose a threat to the very biodiversity of the oceans. Countries grouped around the International Maritime Organization (IMO) have been adopting measures to minimize the risks associated with the transport of organisms through the creation of legal mechanisms such as international conventions. This paper presents an analysis of the national legal mechanisms adopted over the past decades in Colombia (1980-2024) and the legal repercussions arising from the recent ratification and presidential sanction of the International Ballast Water Management Convention (BWM Convention) of 2004 through Law 2362 of 2024.